2019
DOI: 10.1098/rsbl.2019.0574
|View full text |Cite
|
Sign up to set email alerts
|

Does urbanization favour exotic bee species? Implications for the conservation of native bees in cities

Abstract: A growing body of research indicates that cities can support diverse bee communities. However, urbanization may disproportionately benefit exotic bees, potentially to the detriment of native species. We examined the influence of urbanization on exotic and native bees using two datasets from Michigan, USA. We found that urbanization positively influenced exotic—but not native—bee abundance and richness, and that this association could not be explained by proximity to international ports of entry, prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 47 publications
1
43
0
1
Order By: Relevance
“…Our finding that increasing floral resources only mediates plant reproductive success when pollinator richness is high is pertinent because urbanization is associated with increased homogenization of pollinator communities (Deguines et al 2016;Harrison et al 2018;Fitch et al 2019;Wilson and Jamieson 2019). In rural agricultural systems, Kleijn et al found that a few abundant species provide the bulk of , but our findings suggest that the importance of pollinator richness likely varies between urban systems and rural agricultural systems, possibly because resource pulses in urban systems are not predictably constrained to seasonable mass-bloom events.…”
Section: Local Landscape and Pollinator Impacts On Pollinationmentioning
confidence: 58%
“…Our finding that increasing floral resources only mediates plant reproductive success when pollinator richness is high is pertinent because urbanization is associated with increased homogenization of pollinator communities (Deguines et al 2016;Harrison et al 2018;Fitch et al 2019;Wilson and Jamieson 2019). In rural agricultural systems, Kleijn et al found that a few abundant species provide the bulk of , but our findings suggest that the importance of pollinator richness likely varies between urban systems and rural agricultural systems, possibly because resource pulses in urban systems are not predictably constrained to seasonable mass-bloom events.…”
Section: Local Landscape and Pollinator Impacts On Pollinationmentioning
confidence: 58%
“…Impervious cover in some counties increased by as much as 30.5% (2180 ha; Yang et al, 2018). In urbanizing landscapes like our study region, exotic‐bee abundance will almost certainly continue to increase, with unknown consequences for native‐bee communities (Fitch et al, 2019; Russo, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Studies in other cities in eastern US and Canada found similar results (Matteson et al, 2008; Normandin et al, 2017), while crops and natural habitat in Eastern Canada supported only five exotic species (Grixti & Packer, 2006; Sheffield et al, 2003). Most of the urban exotic species in our study region are cavity nesters (see Section 3.1 and Table S3), and increased abundance of exotic bees in cities has not been linked to proximity to ports, urban warming, or abundance of exotic floral resources, leaving increased availability of cavity nest sites as a likely driver (Fitch et al, 2019). Between 2001 and 2016 in our study region, total impervious cover associated with developed land increased by 13.4%, which represents an additional 18,426 ha of impermeable surfaces (Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As exotic bees are often common in urban areas (e.g. Fitch et al 2019), it is noteworthy that all bee species collected by us are native to Germany. It will be interesting to see if the likely spread of exotic bees in the area (Le Féon et al 2018) will influence plant-pollinator interactions.…”
Section: Seasonal Changes Of Plant-pollinator Interaction Networkmentioning
confidence: 88%